MEDIA DI LINGKUNGAN SEKOLAH SEBAGAI SARANA PENINGKATAN KETERAMPILAN MENULIS ANAK - Gusmaniarti, Gusmaniarti; Wahono; Suweleh, Wardah; Dewi, Rida Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop children's writing skills by utilizing media available in their environment such as land media. This research uses quantitative, with a pre-experimental research design with a one-group pre test-post test design type, in this research the researcher used 2 classes which were an experimental class with a total of 21 children and a control class with a total of 20 children. The stages in this research include pre -test, treatment (giving treatment), and post-test. The data collection technique uses observation and documentation techniques. Data analysis uses the Normality Test where when tested using SPPS, (2-tailed) < 0.05, namely at the posttest of the experimental class 0.000. Homogeneity test The results of the output table above show significance with a value of 0.563. Because the significance is more than 0.005, it can be concluded that the two groups have the same variance or that both data are homogeneous. Wilcoxon Test From the calculation of the Wilcoxon Signed Ranks test using SPSS (SPSS Data Attached) then comparing the Sig value and the alpha value resulting from the calculation, the Asymp value is obtained. Sig. (2-tailed) namely 0.000 < 0.05. (Hα) is